1993
DOI: 10.1007/bf00593964
|View full text |Cite
|
Sign up to set email alerts
|

CT demonstration of intracranial haemorrhage in term newborn following vacuum extractor delivery

Abstract: Ten term newborns underwent CT of the brain 12-24 h following vacuum extractor delivery. Haemorrhage in the area of the tentorium was demonstrated in all of them, with similar findings in all cases. CT 1 week later demonstrated reabsorption of the blood without demonstrating any other brain pathology. Clinical and CT examination a year after delivery did not reveal any abnormality. The haemorrhage appears to be a benign condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Our findings are in keeping with those of Avrahami et al [2], who found no residual sequelae on the follow-up CT brain examination of 10 term vacuum-extracted infants who had presented initially with ICH. None of their patients were asphyxiated or had intra-axial extension of bleeding.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are in keeping with those of Avrahami et al [2], who found no residual sequelae on the follow-up CT brain examination of 10 term vacuum-extracted infants who had presented initially with ICH. None of their patients were asphyxiated or had intra-axial extension of bleeding.…”
Section: Discussionsupporting
confidence: 94%
“…Since then, clinically insignificant ICH -usually subarachnoid hemorrhage in the posterior fossa -has been seen with increasing frequency [1]. There have been conflicting reports regarding the sequelae of vacuum extraction-related ICH [2,3]. Furthermore, there is a paucity of reports on the radiological characteristics and sequelae of ICH associated with breech delivery.…”
Section: Introductionmentioning
confidence: 98%
“…Intracranial trauma is more serious and has been reported in paediatric journals. Avrahami et al 27 , using CT scanning, found bleeding around the tentorium in all ten babies examined after vacuum extraction, though it is not clear whether this was a selected group. Subsequent scans showed reabsorption of the blood one week later and no abnormality at one year.…”
mentioning
confidence: 97%
“…It has been suggested that feeding difficulties and irritability might be caused by small amounts of blood in the area of the tentorium that have been found on CT images of the brain in these infants 12-24 h following vacuum extractor delivery. These small amounts of blood seem to be innocent and disappear completely within 1 week without demonstrating any other brain pathology or late neurological sequelae [3].…”
Section: Discussionmentioning
confidence: 99%
“…The use of vacuum extraction is associated with mild to moderate morbidity such as transient hyperbilirubinemia [19,15], pain [17], hematoma or other skin traumata [12,18,19,[23][24][25][26], and transient retinal hemorrhage [8,[10][11][12]. More serious morbidity is described too such as skull fractures [10,14,19,20,23] and intracranial hemorrhages [3,5,9,12,14,19,[22][23][24][25]. Mild to moderate neonatal morbidity occurs frequently, whereas serious neonatal morbidity is rare [12,19,24].…”
Section: Introductionmentioning
confidence: 99%